PENGARUH KARAKTERISTIK TIM, DAN KEPERCAYAAN TERHADAP KINERJA PEGAWAI TATA USAHA SMA NEGERI DI KABUPATEN BONE PROVINSI SULAWESI SELATAN - Syamsuddin Syamsuddin (Jurnal Manajemen Pendidikan, 2013)
The aim of this research is to examine the effect of team characteristic and trust on job performance. The Research has been implemented by using path analysis, after all variables put into a matrix of correlation. In this research, employees had been choosen as a unit analysis and 104 samples selected by randomly. The result of research indicates : (1) there is direct effect of team characteristic on job performance, (2) there is direct effect of trust on job performance, (3) there is direct effect of team characteristic on trust. Based on those finding it could be concluded that any changing or variation wich occured to the job performance of administration employees of State Senior High School at Bone Regency in South Sulawesi Province had been effected by team characteristic and trust.